The Luminaries - Catton, Eleanor (Wellington, N.Z Victoria University Press, 2013)
It is 1866, and Walter Moody has come to make his fortune upon the West Coast goldfields. On the night of his arrival, he stumbles across a tense gathering of twelve local men, who have met in secret to discuss a series of unsolved crimes. A wealthy man has vanished, a whore has tried to end her life, and an enormous sum of money has been discovered in the home of a luckless drunk. Moody is soon drawn into the mystery: a network of fates and fortunes that is as complex and exquisitely patterned as the night sky.
Keywords: New Zealand -- Hokitika